2015
DOI: 10.1039/c5tc00530b
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric properties of individual nanocrystallites of Ba0.85Ca0.15Zr0.1Ti0.9O3 obtained by oxalate precursor route

Abstract: Ferroelectric domain pattern and piezoresponse (d33) versus DC bias voltage for the BCZT nanocrystalline powder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 39 publications
0
17
1
Order By: Relevance
“…4 (e). From the butterfly curve showed in panel 4 (d), the effective piezoelectric coefficient (d 33 ) value 35 was estimated through the following equation of the law of converse of piezoelectric effect 32,[36][37][38] : (1) where D is the measured value of piezoelectric displacement, V is the applied voltage, and D 1 and V 1 are the piezoelectric displacement and applied voltage of the intersection …”
Section: Panel (A) Inmentioning
confidence: 99%
“…4 (e). From the butterfly curve showed in panel 4 (d), the effective piezoelectric coefficient (d 33 ) value 35 was estimated through the following equation of the law of converse of piezoelectric effect 32,[36][37][38] : (1) where D is the measured value of piezoelectric displacement, V is the applied voltage, and D 1 and V 1 are the piezoelectric displacement and applied voltage of the intersection …”
Section: Panel (A) Inmentioning
confidence: 99%
“…The value of d 33 increased with increasing grain size (The wide variation in d 33 may be verified further with the communicated “”). It should be noted that different localized piezoelectric responses from piezoelectric grains having different grain size were also reported earlier . Since the D‐V butterfly curves were unsymmetrical, obtaining a constant d 33 on either side of the voltage axis (+ve or −ve) was not possible, although the PFM experiments were performed using a properly calibrated PFM measurement set up.…”
Section: Resultsmentioning
confidence: 86%
“…The reports on piezoelectric response of a plethora of perovskite ferroelectric materials, BaTiO 3, LiNbO 3 , K 0.5 Na 0.5 NbO 3 , BCZT etc. at nanoscale has been studied . For instance, Emelianov et al reported the piezoelectric coefficient, ( d 33 ) to be 27 pm/V for BaTiO 3 nanoparticles (spherical shape, diameter of 20–200 nm) with surface‐modified hydroxyl groups.…”
Section: Introductionmentioning
confidence: 99%
“…at nanoscale has been studied. [18][19][20][21] For instance, Emelianov et al 18 reported the piezoelectric coefficient, (d 33 ) to be 27 pm/V for BaTiO 3 nanoparticles (spherical shape, diameter of 20-200 nm) with surface-modified hydroxyl groups. The reported piezoelectric coefficients (d 33 ) were 17 and 12 pm/V for LiNbO 3 nanoparticles of cube-like shape and spherical shape, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation